Effects of grain size and grain geometries on residual oil saturation after water flooding - Yunan, Mat Hussin (Penerbit UTM Press, 2008)
This paper presents an experimental study on the effect of grains size and grain geometry on residual oil saturation after water flooding. Cylindrical sand pack holder (2.5 cm Ã— 30.5 cm) was developed and all variables except grain size and grain geometry were kept constant during the water flood experiment. The flow rates of water flooding process in this experiment were set to 11 ml/min, crude oil as a displaced fluid and NaCl solution (brine) with 20,000 ppm concentration was used as a displacing fluid injected into the sand pack. The result from the first part of the experiment revealed that grain with size from 250 â€“ 500 (Î¼m) produce the highest residual oil saturation, while grain with 1000-2000 (Î¼m) size recovers more oil. Second part of the study show that angular grain geometry with (80% glass bead + 20% sand) produced the highest residual oil saturation, indicating an effect on residual oil saturation due to grain geometry, while percentage of oil recovery varies when there is an increase of percentage of sand in sand pack consist of glass bead. The result of this study showed that grain size and grain geometry have a measurable effect on residual oil saturation after water flooding.